2000
DOI: 10.1159/000053210
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Juvenile Rheumatoid Arthritis with Growth Hormone

Abstract: Severe growth retardation and profoundly altered body composition are observed in children with juvenile chronic arthritis receiving glucocorticoids. This study assessed the effects of growth hormone (GH) on height velocity, body composition and bone density. Fourteen patients were treated with GH (1.4 U/kg/week) for 1 year and then studied for a 2nd year off GH. The treatment increased insulin-like growth factor 1 and insulin-like growth factor binding protein 3 plasma levels. All patients showed an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…The investigators found an increase in bone mineral content and height as well as in osteocalcin levels, which correlated with height velocity. Simon et al (102) reported nearly identical results in their rHGH trial. The standard dose of rHGH given to children with growth hormone deficiency is 0.05 mg/kg/d.…”
Section: Management Of Giblmentioning
confidence: 80%
“…The investigators found an increase in bone mineral content and height as well as in osteocalcin levels, which correlated with height velocity. Simon et al (102) reported nearly identical results in their rHGH trial. The standard dose of rHGH given to children with growth hormone deficiency is 0.05 mg/kg/d.…”
Section: Management Of Giblmentioning
confidence: 80%
“…Growth hormone was effective in stimulating collagen production and improving liner growth in JIA [81–83]. However, long-term controlled studies are needed to determine impact on bone mass and bone turnover and the risks of growth hormone therapy [84].…”
Section: Therapeutic Options To Improve Bone Status In Jiamentioning
confidence: 99%
“…Growth hormone studies reveal a state of mild GH resistance with normal GH secretion and mildly low Brought to you by | Biblioteca de la Universidad de Sevilla Authenticated Download Date | 6/16/15 10:20 AM IGF-1 levels. Growth hormone treatment is not approved by the FDA for JRA but has been used in a clinical trial in which an increase in the rate of linear growth was shown (52,53).…”
Section: Rheumatologic Disordersmentioning
confidence: 99%